Encapsulation of Trichoderma harzianum Preserves Enzymatic Activity and Enhances the Potential for Biological Control - Maruyama, Cintia Rodrigues; Bilesky-José, Natália; de Lima, Renata; Fraceto, Leonardo Fernandes (Frontiers in Bioengineering and Biotechnology, 2020)
Trichoderma harzianum is a biological control agent used against phytopathogens and biostimulation in agriculture. However, its efficacy can be affected by biotic and abiotic factors, and microencapsulation has been used to maximize the efficacy. The objective was to develop polymeric microparticles to encapsulate T. harzianum, to perform physicochemical characterization to evaluate its stability, to evaluate effects on the soil microbiota, antifungal activity in vitro and enzymatic activity. Size distribution of wet and dry microparticles was 2000 and 800 μm respectively. Scanning electron microscopy showed spherical morphology and encapsulation of T. harzianum. Photo-stability assays showed that encapsulation protected the fungus against ultraviolet radiation. The evaluation of the microbiota showed that the proportion of denitrifying bacteria increased when compared to the control. The T. harzianum encapsulation showed an improvement in the chitinolytic and cellulosic activity. In vitro tests showed that encapsulated fungus were able to provide a greater control of S. sclerotiorum.